OPTIMUM DENSITY OF Nannochloropsis sp. FOR MASS SCALE CORAL TROUT, Plectropomus leopardus (Lacepède, 1802) - Yasmina Nirmala Asih; Sudewi Sudewi; Afifah Nasukha; Daniar Kusumawati; Ketut Mahardika; Ahmad Muzaki; I Nyoman Adiasmara Giri (Indonesian Aquaculture Journal, 2020)
Coral trout, Plectropomus leopardus (Lacepède, 1802)is a visual feeder. Turbidity caused by phytoplankton or clay particle in the water will affect the visual foraging of coral trout larvae. Addition of Nannochloropsis sp. has been included in standard operational procedure for marine fish larval rearing as green water. However, the density of Nannochlorposis sp. in coral trout larval rearing system has not been evaluated. This study aimed to evaluate the optimal of Nannochloropsis sp. required for rearing of coral trout larvae. Nannochloropsis sp. was given to two days old larvae (D-2), with the densities of 2 x 105, 4 x 105, and 6 x 105cell/mL. After 50 days rearing period (D-50), evaluation on the average size and total harvest were recorded. The results showed that the density of 2 x 105 cell/mL Nannochloropsis sp. was the best in survival rate (2.35 ± 1.05%) than other densities, but they were not significantly different (P>0.05) than those of 4 x 105 cell/mL (1.67 ± 0.70%) and 6 x 105 cell/mL (1.26 ± 1.05%). The lower densities, 2 x 105 and 4 x 105cell/mL, were dominated by more than 50% of > 2.7 cm sized juvenile. Histological analysis of fish eyes supported that the two lower densities produced dominant cone shape as the receptor cells in the retina observed. From an economical aspect, addition of 2 x 105 cells/mL resulted on the higher profit, hence optimum density of Nannochloropsis sp. added in coral trout larval rearing on a mass scale was 2 x 105 cells/mL.